Europe's role in nation-building : from the Balkans to the Congo - Dobbins, James, 1942- (RAND Corp., 2008)
Since 1989, nation-building has become a growth industry. In two prior volumes, RAND has analyzed the United States' and United Nations' (UN's) performance in this sphere, examining instances in which one or the other led such operations. In this monograph, we look at Europe's performance, taking six instances in which European institutions or national governments have exercised comparable leadership. To complete our survey of modern nation-building, we have also included a chapter describing Australia's operation in the Solomon Islands. In previous volumes, we defined nation-building as the use of armed force in the aftermath of a conflict to promote a durable peace and representative government. By specifying the use of armed force, we are not suggesting that compulsion is always necessary or even desirable, nor do we mean to imply that only armed force is used in such missions. The European Union has, indeed, become quite adept at mounting nonmilitary interventions in support of conflict resolution. We do believe that peace operations that include a military component can be usefully grouped together for analytical purposes, however, since the employment of force and the integration of military and civil instruments impose particular demands. Neither, in employing the term nation-building to describe this activity, are we seeking to distinguish it from what the United Nations calls peace-building, what the U.S. government calls stabilization and reconstruction, and what many European governments prefer to call state-building. Nation-building is the term most commonly used in American parlance, but any of these other phrases may serve equally well; those who prefer can substitute one or the other without injury to our argument. This is not a comprehensive study of all nation-building operations that have involved European countries. European troops, police, civilian advisers, and money have supported nearly every such operation over the past 60 years. Rather, it is a study of the European role in six cases in which the European Union or a European government led all or a key part of such an operation: Albania, Sierra Leone, Macedonia, Côte d'Ivoire, the Democratic Republic of the Congo, and Bosnia. There are obvious difficulties in distinguishing among U.S.-, UN-, and European-led nation-building, since many international peace operations involve the participation of all three. Nevertheless, it should make a difference whether military command is being exercised from Washington, New York, Brussels, Paris, or London. This study was intended to explore those differences. Previous volumes looked at the distinctive U.S. and UN approaches to these sorts of missions. This one seeks to determine whether there is an identifiable European way of nation-building, and if so, what we can learn from it. All eight of the U.S.-led operations studied in the first volume were "green-helmeted": They were commanded by the U.S. military or the North Atlantic Treaty Organization (NATO), at least at some point in their evolution. All nine of the UN-led cases in the second volume were "blue-helmeted": They were directed by the UN secretary-general and local UN representatives. In principle, there is a clear distinction between the two types of command, even if several of the operations did move from one category to the other over the course of their conduct. Somalia, for example, started as a UN-led mission, transitioned to U.S. command, and then became a hybrid mission, with troops under UN and U.S. command operating side by side. All of the operations in this volume were green-helmeted, in whole or in part. Albania was a nationally (Italian) commanded operation. Macedonia began as a NATO operation and was taken over by the European Union. Bosnia followed a similar path, beginning as a UN-led mission, transitioning to NATO command and, later, to EU command. The Democratic Republic of the Congo, a UN-led operation, experienced two insertions of independently commanded EU forces. Sierra Leone and Côte d'Ivoire were also UN-led missions, alongside which nationally commanded British and French troops conducted independent operations. In previous volumes, we looked at the Bosnia and Sierra Leone cases from the NATO and UN perspectives. Here, we examine more closely the roles of Britain and France in those same operations. All these European cases had UN Security Council (UNSC) mandates at some stage in their evolution. By contrast, the Australian led multinational intervention in the Solomon Islands, also included in this volume, functioned without major UN, European, or U.S.involvement.--Excerpted from Summary, p. xv-xvii.